Barbados : First Review under the Extended Arrangement and Request for the Completion of the Financing Assurances Review and Modification of Performance Criteria. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2019)
First Review under the Extended Arrangement and Request for the Completion of the Financing Assurances Review and Modification of Performance Criteria - Press Release; Staff Report; and Statement by the Executive Director for Barbados.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet